2015
DOI: 10.1039/c5py00089k
|View full text |Cite
|
Sign up to set email alerts
|

Glyconanoparticles and their interactions with lectins

Abstract: Recent progress in nanobiotechnology has allowed the use of glycans and their conjugates as biofunctional molecules for many biological and biomedical applications. Therefore, specific interactions of carbohydrate-binding proteins (lectins) are continuously being elucidated for a deep understanding of their functions and the precise mechanism of their association with specific ligands. New generations of glyconanoparticles with outstanding features that present carbohydrates in a multivalent manner and locally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 78 publications
0
100
0
Order By: Relevance
“…While this capacity to control cell organization has previously been demonstrated with peptide functionalized aligned fiber polymers, this is the first time that a synthetic glycopolymer has been shown to exhibit the same effect on cell attachment. Previous studies have demonstrated that synthetic glycopolymers can interact specifically with human C‐type lectins and the sequence of sugar moieties diversifies the specific interaction, potentially explain this promising cell–material interaction. However, the mechanisms by which tenocytes interact with glycopolymers needs to be addressed by further study.…”
Section: Resultsmentioning
confidence: 99%
“…While this capacity to control cell organization has previously been demonstrated with peptide functionalized aligned fiber polymers, this is the first time that a synthetic glycopolymer has been shown to exhibit the same effect on cell attachment. Previous studies have demonstrated that synthetic glycopolymers can interact specifically with human C‐type lectins and the sequence of sugar moieties diversifies the specific interaction, potentially explain this promising cell–material interaction. However, the mechanisms by which tenocytes interact with glycopolymers needs to be addressed by further study.…”
Section: Resultsmentioning
confidence: 99%
“…The attachment of carbohydrates to MNPs can be used to form glycoMNPs to selectively interact with cells, as carbohydrateinteracting proteins are major components of the surface of mammalian cells [70].…”
Section: Cell Targetingmentioning
confidence: 99%
“…In so doing, targeted nanocarriers have been fabricated to harness saccharide ligands whose receptors play central roles in various functions within the body, such as fertilization, immunity and growth. Glyco‐nanoparticles have been prepared via either the self‐assembly of glycopolymers or the decoration of nanoparticle shells with various monosaccharides to promote their interaction with cells that express monosaccharide ligand receptors. Macrophages and immature dendritic cells bear the monosaccharide–ligand receptor macrophage mannose receptor (cluster of differentiation 206, CD206), a C‐type lectin, on their surface that recognizes terminal mannose, fructose and N ‐acetylglucosamine .…”
Section: Targeted Bio‐functionalities Of Saccharide‐based Nanocarriersmentioning
confidence: 99%